Functionalisation of spider silk protein 4RepCT using un-natural amino acid mutagenesis and click chemistry - Harvey, David J. (2017)
Interest in spider silk as a biomaterial has recently increased owing to its strength, biocompatibility, biodegradability, lack of immunogenicity and pyrogenicity. Unfortunately large scale production from spiders is highly impractical, as their cannibalistic nature prevents them from being farmed. As a consequence of this, scalable production of recombinant spider silk sequences in E.coli has emerged. There is a demand for functionalised silk materials tailored for specific novel applications. Previously this has been achieved through genetic fusion, which can prove difficult when using highly GC rich silk sequences, or classical chemical conjugation methods that are non-residue or non-site specific. The aim of the research described in this thesis was to produce a chemically modifiable self-assembling spider silk protein through the incorporation of a non-canonical amino acid into a miniature spidroin construct (4RepCT). To achieve this, a methionine auxotrophic strain of E.coli has been used to incorporate a methionine analogue (L-azidohomoalanine (L-Aha)) in place of all three methionine residues in the mature 4RepCT sequence to give 4RepCT3Aha. I have demonstrated that this did not adversely affect the normal self-assembly process of the protein into fibres. Subsequently the silk protein was functionalised using either copper-catalysed azide-alkyne cycloaddition (CuAAC) or strain-promoted azide-alkyne cycloaddition (SPAAC) in so called click chemistry reactions for a number of purposes. Firstly, the presence of 2 L-Aha residues was verified by the successful conjugation of alkyne modified fluorophores to both soluble spidroin protein and pre-made fibres. Following this proof of principle 4RepCT3Aha fibres were then functionalised with the broad spectrum antibiotic levofloxacin endowing the fibres with antimicrobial activity which has been demonstrated against E.coli NCTC 12242. Another potential area of application for spider silk is as a cell scaffold for use in wound healing and tissue engineering. 4RepCT3Aha has been modified through conjugation of alkyne modified cyclic peptides bearing an RGD motif to improve its capacity to support mesenchymal stem cells. This was demonstrated to be more effective in supporting growth of the cells compared to routinely used tissue culture plastics. The successful modifications of 4RepCT3Aha reported in this thesis highlight the versatility of the residue-specific click chemistry modification approach, generating new bespoke silk-based materials relevant in a wide range of applications.